(3fTQ GdeWjH ai GdYed HGdQHY GdeLjHs - (3GdTGaYj, GHf RQjb, eMeO Hf EHQGgje Hf Ydj Hf RQjb, J (B977 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj YdefG eG de fcf fYde SCdfj HYV GdCUMGH hNdGUI GdCMHGH Cf GLeY dg gPg GdQSGdI eNJUQI eajOI aj GdYed HGdQHY GdeLjH aCLHJ SDGdg hLeYJ dg gPg GdQSGdIs
(3BNQgG (B:s
(3Pdc GdbGFe dCf CQHY CUGHY gj KdK GdbGFeI hYdi gPG GdbjGT abS HYO Gf JYde Gf GdbGeI GKfj YTQ GUHYG aGdUdGUI QHYgG hGdCQHYI KdKG Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\303s
(3EjVGM Gdecfhf (B2\648s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs